Free trade means destabilisation - Wolfgang Hager (Intereconomics, 1984)
There seems to exist wides pread agreement on the superiority of free trade over other forms of trading systems with protectionism being accepted, at best, as a temporary device for slowing down adjustment processes. As against that, Dr. Hager argues that the markets of industrialised and developing countries can only destabilise each other when linked by an international megamarket. He there fore advacates an alternative trading order involving managed trade.
Keywords: 330; Trade Policy